Pengaruh Konsentrasi Fraksi Etil Asetat Bangle Terhadap Nilai SPF Krim Ekstrak Temugiring - Anisa Lailatusy Syarifah; Andini Andini; Haritsah Alfad (Fakultas Farmasi Universitas Pancasila, 2022)
The concentration of bangle (Zingiber cassumunar) ethyl acetate fraction added in the formulation of the temugiring (Curcuma heyneana) extract cream formulation must be determined precisely since it may affect the Sun Protection Factor (SPF) value. This research aims to determine the effect of concentration variations of bangle ethyl acetate fraction on the SPF value of the temugiring extract cream. In this research, temugiring extract and bangle extract were obtained by remaceration employing ethanol, while the bangle ethyl acetate fraction was obtained by fractionation using n-hexane, ethyl acetate, methanol, and water. The bangle ethyl acetate fraction obtained was formulated in cream formulations of temugiring extract formulas 1, 2, and 3 with variations in the concentration of bangle ethyl acetate fraction 2%; 3%; and 4%. Furthermore, the SPF value was conducted using the UV-Vis spectrophotometry method. The results show that bangle ethyl acetate fraction concentration variations produced different SPF values for each cream formula. The SPF value for formulas 1, 2, and 3 was 11.466; 12.122; and 17.266. One Way ANOVA test produced a p-value of 0.037. Thus, it can be concluded that the concentration of the bangle ethyl acetate fraction would affect the SPF value in the cream temugiring extract.